Pelatihan Pengolahan Limbah Pertanian Sebagai Hijauan Makanan Ternak Desa Tanjung Rejo, Lampung - Harfina Rais; Nani Irwani; Intan Kamilia Habsari; Desi Maria Sinaga; Heni Suryani; Gusma Gama Maradon (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
The role of education in higher education is very important to prepare students to become individuals who have the ability to be able to develop themselves further. Based on the results of a field survey, data on students who continue their tertiary education in Langkaplancar Village are still lacking, and their motivation to continue on to tertiary education is still low. The reality is that currently in Langkaplancar Village there are many high school graduates/equivalents who decide not to continue their education at tertiary institutions, some choose to work or even become unemployed, due to economic factors and lack of motivation. One of the efforts made to solve this problem is holding an Education Motivation Training Seminar. The purpose of this activity is to increase student motivation to continue their studies at tertiary institutions and to raise awareness of all parties, especially parents, in providing support for children to continue on to tertiary institutions. The results of this community service activity are (1) Socialization and coordination with related elements (2) Implementation of activities and (3) Responses of the Village Government, School Principals, Teachers and Parents to activities.